Residual Income Risk, Intrinsic Values, and Share Prices - Baginski, Stephen P.; Wahlen, James M. (The Accounting Review, 2003)
Empirical accounting research provides surprisingly little evidence on whether accounting earnings numbers capture cross-sectional differences in risk that are associated with cross-sectional differences in share prices. We address two questions regarding the risk-relevance of accounting numbers: (1) Are accounting-related risk measures (i.e., the systematic risk and total volatility in a firm's time-series of residual return on equity) associated with the market's assessment and pricing of equity risk? (2) If so, then are these accounting-related risk measures incrementally associated with the market's assessment and pricing of equity risk beyond other observable factors, such as those in the Fama and French (1992) three-factor model? We develop an accounting-fundamentals-based measure of the market's pricing of risk—the difference between actual share price and a residual income valuation model estimate of share value using risk-free rates of return. Our results show that both systematic risk and total volatility in residual return on equity partially explain this pricing differential, and that the explanatory power of total volatility is incremental to the Fama and French (1992) factors—market beta, firm size, and the market-to-book ratio.